Efficiency of zeolite and apatite on the mobility of heavy metals in the soil through the Sinapis Alba as test culture - Marija Kojić; Časlav Lačnjevac; Rakočević Ljiljana Bošković (Zaštita Materijala)
Protection and improvement of the environment, especially preservation and protection of the land, has become one of the most important problems of the modern world today. The research in this paper aims at examining the efficiency of two types of mineral raw materials, zeolites and apatites on the immobilization of heavy metals and preventing their inclusion in the food chain. Pb, Cd, Zn and radionuclides (U) were tested. In doses 10 mg kg-1Cd, 500 mg kg-1 Pb, 300 mg kg-1Zn i 300 mg kg-1U. On soil with various physico-chemical properties (sandy chernozem and pseudocley). The efficiency of mineral resources through the adsorption / precipitation of pollutants in the soil was investigated through vegetation experiments with the test culture-plant, Sinapis Alba, through the contents of Pb, Cd, Zn and U in the root and overgrowth mass. The results indicate that both, zeolite and apatite in dosage 20 g kg-1 soils, have contributed to the immobilization of the investigated pollutants, that their effectiveness depends of soils type and their acidity, kinds of pollutant, so their use is justified in the application of technologies for the remediation of contaminated soils in the function of sustainability of agricultural production and the production of healthy food.